(untitled) (Al-Mansour Journal, 2023)
This research aims at identifying the expectation gap between those who take benefit from auditors and auditing actual reality represented by its public purposes, auditors’ real qualifications, actual duties and responsibilities, and their domains. This unavoidable, real gap must be fronted and treated as one of the main outstanding auditing difficulties. The auditing standards, local or international, is one of the procedures and tools to solve this problem by defining its auditing and auditors’ actual responsibilities and tasks to those beneficent of the results of the auditing process .This in turn will help to decrease this misunderstanding between the two parties. The present research hypothesized that auditing standards play such an influential role in reducing this expectation gap, which in turn will achieve the research main aim at defining the role of these auditing standards in reducing this expectation gap. This can lead to adopt these standards as a procedure for solving the problem under study.